The Sacred and the secular in India's performing arts : Ananda K. Coomaraswamy centenary essays - Coomaraswamy, Ananda Kentish, 1877-1947; Subramaniam, Venkateswarier, 1920- (Ashish, 1980)
Contributed articles.